A "copolymer-co-morphology" conception for shape-controlled synthesis of Prussian blue analogues and as-derived spinel oxides. Issue 4 (11th January 2016) - Li, Xuning; Yuan, Lizhi; Wang, Junhu; Jiang, Luhua; Rykov, Alexandre I.; Nagy, Dénes L.; Bogdán, Csilla; Ahmed, Mamdouh A.; Zhu, Kaiyue; Sun, Gongquan; Yang, Weishen
Abstract : The morphologically and compositionally controlled synthesis of coordination polymers and spinel oxides is highly desirable for realizing new advanced nanomaterial functionalities. Abstract : The morphologically and compositionally controlled synthesis of coordination polymers and spinel oxides is highly desirable for realizing new advanced nanomaterial functionalities. Here we develop a novel and scalable strategy, containing a "copolymer-co-morphology" conception, to shape-controlled synthesis of various types of Prussian blue analogues (PBAs). Three series of PBAs M y Fe1− y [Co(CN)6 ]0.67 · n H2 O (M y Fe1− y –Co, M = Co, Mn and Zn) with well-controlled morphology have been successfully prepared through this strategy. Using Mn y Fe1− y –Co PBAs as the model, by increasing the relative content of Mn, flexible modulation of the morphology could be easily realized. In addition, a series of porous Mn x Fe1.8− x Co1.2 O4 nano-dices with well-inherited morphologies and defined cation distribution could be obtained through a simple thermal treatment of the PBAs. All these results demonstrate the good universality of this novel strategy. When evaluated as an electrocatalyst, the octahedral-site Mn III /Mn IV content in Mn x Fe1.8− x Co1.2 O4, mainly determined by sensitive 57 Fe Mössbauer in combination with X-ray photoelectron spectroscopic techniques, was discovered to be directly correlated with the oxygen reduction/evolution reaction (ORR/OER) activity.